Prognostic Significance of Ultrasound Findings of Acute Acalculous Cholecystitis for Elderly Long-Term Bedridden Patients - Lin, Qian; Shen, Lei; Chen, Cheng; Yang, Zhen; Que, Yifan; Liu, Yani; Yin, Ming; Xu, Guogang; Li, Junlai (Frontiers in Medicine, 2021)
Background: Acute acalculous cholecystitis (AAC) is characterized by the development of cholecystitis in the gallbladder without gallstones or with small gallstones unrelated to inflammatory diseases. This disease is not rare in the elderly bedridden patients with co-morbidities and prone to develop life-threatening gangrene or perforation of gallbladder. Early imaging is essential for detecting and effectively treating AAC. This study aimed to evaluate the use of ultrasound diagnostic criteria for the diagnosis and prognosis of elderly long-term bedridden patients with suspected AAC. Methods: We retrospectively studied 374 elderly bedridden patients with clinical manifestations of AC at the acute stage of the disease. Gallbladder anomalies were found in 92 patients by ultrasound examination, which correlated with the duration time of clinical manifestations, complications, as well as therapeutic prognosis. The major and minor ultrasound criteria of AAC were made according to the Tokyo Guidelines 2018. Ultrasound results were thought to be AAC positive when they met two major criteria or one major and two minor criteria. Results: Forty-three (46.7%) of the 92 patients presented with AAC (+) test results based on the ultrasound criteria, with a higher incidence of complications (27.9%) than AAC (–) patients (0%; P < 0.001). The median length of symptoms (8 vs. 4 days, P < 0.001) and duration of antibiotic therapy (13 vs. 5 days, P < 0.001) were longer in the AAC (+) group. Conclusions: The ultrasound-based AAC (+) group often had a worse prognosis than the AAC (–) group. Therefore, patients from the AAC (+) group should receive a follow-up ultrasound examination to detect disease progression early.